Investigation and Design of Mobile OPAC Services (MOS) for Non-Smartphone Users - Vasudavan, Hemalata (Information Management and Business Review, 2013)
This research focuses on providing Online Public Access Catalog services to university students via mobile phone in order to enhance the traditional library walk in services and online library access using a computer. This research comprises of three main findings in relation with mobile OPAC services. First, it investigates student’s perception in using mobile phone to access OPAC services in the educational environment. Next, it identifies and adopts mobile content design guidelines in the development of Mobile OPAC Services (MOS) prototype application. Third, it develops MOS prototype Application for NonSmartphone users. Quantitative and qualitative data analysis techniques conducted to identify student’s uses and needs for mobile library services access. The survey derived 73% of the students prefer to access the Online Public Access Catalog (OPAC) via mobile phone. The reason being is that OPAC provide major services of the library such as searching for learning materials, new titles in the library, reservation list and other related services. By conducting the survey, we discovered 71% of the students are using non-smart phone because they are still studying and unable to buy a smart phone which is expensive. Based on this finding we design a Mobile OPAC Service (MOS) prototype application for university students to access Online Public Access Catalog services via non-smart phones. The mobile OPAC services will bring libraries one step ahead in the wireless information technology world in meeting their patrons needs and providing quality education resources.